Phylogeny and molecular evolution of the first local monkeypox virus cluster in Guangdong Province, China - Yu, Jianhai; Zhang, Xin; Liu, Jiajun; Xiang, Linlin; Huang, Shen; Xie, Xiaoting; Fang, Ling; Lin, Yifan; Zhang, Meng; Wang, Linqing; He, Jianfeng; Zhang, Bao; et al. (Nature communications, 2023)
The first local mpox outbreak in Guangdong Province, China occurred in June 2023. However, epidemiological data have failed to quickly identify the source and transmission of the outbreak. Here, phylogeny and molecular evolution of 10 monkeypox virus (MPXV) genome sequences from the Guangdong outbreak were characterized, revealing local silent transmissions that may have occurred in Guangdong whose mpox outbreaks suggested a molecular epidemiological correlation with Portugal and several regions of China during the same period. The lineage IIb C.1, which includes all 10 MPXV from Guangdong, shows consistent temporal continuity in both phylogenetic characteristics and unique molecular evolutionary mutation spectrum, reflected in the continuous increase of single nucleotide polymorphisms (SNPs) and shared mutations over time. Compared with the Japan MPXV, the Guangdong MPXV showed higher genomic nucleotide differences and separated 14 shared mutations from the B.1 lineage, comprising 6 non-synonymous mutations in genes linked to host regulation, virus infection, and virus life cycle. The unique mutation spectrum with temporal continuity in IIb C.1, related to apolipoprotein B mRNA-editing catalytic polypeptide-like 3, promotes rapid viral evolution and diversification. The findings contribute to understanding the ongoing mpox outbreak in China and offer insights for developing joint prevention and control strategies. The first known local mpox outbreak in Guangdong Province, China occurred in June 2023. Here, the authors perform phylogenetic and molecular evolution analysis of ten mpox virus genome sequences from this outbreak, and place them in the context of other samples detected in surrounding regions.